Project for a train station - Suárez Pastrana, Héctor (La Estructura en el Proyecto de Arquitectura, 2015)
The current project was proposed in 2011 as a part of the course of study “Structural Designs 2”, which is taught by Javier Estévez Cimadevila, professor of structures in the ETSAC (the Architecture School of La Coruña). We were asked to design a single-span structure to cover the three railway platforms which take up 50 meters wide, besides saving some space for several stores and offices.